Accounting for intangibles and intellectual capital : a literature review from 2000 to 2020 - Garanina, Tatiana; Hussinki, Henri; Dumay, Johannes (Wiley, 2021)
This article presents the results of a systematic literature review on intangibles and intellectual capital (IC) focusing on articles published in the top 20 accounting journals between 2000 and 2020. We find that North American accounting scholarship during this period has predominantly focused on identifiable intangibles and how these appear in the balance sheet. Much less attention has been given to management issues and IC, even though these issues are more common in European and Australian accounting literature. By evaluating recent developments and trends, this contribution aims at identifying promising avenues for future research endeavours.
Keywords: Intangible assets; Intellectual capital; Intangibles; Structured literature review; accounting; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|